2017
DOI: 10.1017/dmp.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Recovery From Hurricane Sandy: Evidence From a Survey in New York City

Abstract: The study outlines the critical importance of health and socioeconomic factors in long-term disaster recovery and highlights the need for increased consideration of those factors in post-disaster interventions and recovery monitoring. More research is needed to assess the effectiveness of state and federal assistance programs, particularly among disadvantaged populations. (Disaster Med Public Health Preparedness. 2018;12:172-175).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…The region's vulnerability is further compounded by poor health metrics such as high obesity and diabetes rates, and by socio-economic factors such as chronic poverty and a struggling economy (Arosemena et al, 2013;Goldstein et al, 2011). While disasters do not discriminate who they affect, they disproportionately impact the most vulnerable groups in society (Petkova et al, 2017). Children are particularly vulnerable during disasters due to their physical characteristics, their widely varying stages of development and their reliance on adults for their safety and well-being (Chrisman & Dougherty, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The region's vulnerability is further compounded by poor health metrics such as high obesity and diabetes rates, and by socio-economic factors such as chronic poverty and a struggling economy (Arosemena et al, 2013;Goldstein et al, 2011). While disasters do not discriminate who they affect, they disproportionately impact the most vulnerable groups in society (Petkova et al, 2017). Children are particularly vulnerable during disasters due to their physical characteristics, their widely varying stages of development and their reliance on adults for their safety and well-being (Chrisman & Dougherty, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research focusing on vulnerable populations in public housing affected by Hurricane Sandy, including individuals living in Far Rockaway, has proposed that marginalized populations face a delayed period in recovery stemming from a depleted “resilience–reserve” (Carbone & Wright, ; Hernández et al., ; Petkova et al., ). Essentially, chronic hardships, such as poverty, can decrease these groups’ capacity to have resilience in the face of an acute exposure (e.g., Hurricane Sandy).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on post-Hurricane Sandy recovery has indicated that middle-income homeowners were most vulnerable to flooding [54]. Other studies indicate that lower income individuals and families have experienced more substantial impact as a result of Hurricane Sandy [40,[55][56][57][58], as well as Hurricane Katrina [59][60][61].…”
Section: Discussionmentioning
confidence: 99%